Gender-smart investing to scale climate-smart agriculture in the Ghanaian context - Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This presentation was delivered at the AICCRA-Ghana Public Forum on March 25, 2022 to create awareness on how mainstreaming gender smart investing can help scale inclusive business models. It highlighted how the integration of gender dimensions in the investment process presents great opportunities to mitigate risks, amplify impacts, and reduce gender inequality.